2019
DOI: 10.35946/arcr.v40.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Disorder and Depressive Disorders

Abstract: Alcohol use disorder (AUD) and depressive disorders are among the most prevalent psychiatric disorders and co-occur more often than expected by chance. The aim of this review is to characterize the prevalence, course, and treatment of co-occurring AUD and depressive disorders. Studies have indicated that the co-occurrence of AUD and depressive disorders is associated with greater severity and worse prognosis for both disorders. Both pharmacologic and behavioral treatments have demonstrated efficacy for this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
240
3
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(275 citation statements)
references
References 54 publications
12
240
3
20
Order By: Relevance
“…Consistent with epidemiological findings that substance use disorders are commonly comorbid with PTSD [ 118 , 119 , 120 , 121 ] and MDD [ 122 , 123 ], there was a higher prevalence of history of alcohol abuse/dependence in MCI group compared to the other two groups (44% vs. 19% and 23% in intermediate and CN). Although post-hoc analysis suggested that history of alcohol use disorder was not significantly associated with MCI status in the present study, like PTSD and MDD, heavy alcohol use has been associated with deleterious effects on the hippocampus [ 124 ] and cognitive function [ 125 , 126 , 127 , 128 ].…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with epidemiological findings that substance use disorders are commonly comorbid with PTSD [ 118 , 119 , 120 , 121 ] and MDD [ 122 , 123 ], there was a higher prevalence of history of alcohol abuse/dependence in MCI group compared to the other two groups (44% vs. 19% and 23% in intermediate and CN). Although post-hoc analysis suggested that history of alcohol use disorder was not significantly associated with MCI status in the present study, like PTSD and MDD, heavy alcohol use has been associated with deleterious effects on the hippocampus [ 124 ] and cognitive function [ 125 , 126 , 127 , 128 ].…”
Section: Discussionsupporting
confidence: 83%
“…Alcohol use disorder: Alcohol use disorder (AUD) was identi ed based on the 10-item Alcohol Use Disorder Identi cation Test (AUDIT), a screening instrument developed by the World Health Organization (WHO), which includes questions on the patterns of hazardous and harmful alcohol use and dependence symptoms in the past 12 months [24]. The respondents were classi ed into three levels based on the AUDIT scores: non-problem drinkers (0-7), hazardous drinkers (8)(9)(10)(11)(12)(13)(14)(15), and harmful-dependent drinkers [24].…”
Section: Methodsmentioning
confidence: 99%
“…Treating depression may decrease pain conditions [36], especially if both pain and depression are most severe at the beginning of treatment [35]. Similarly, the synergistic effects of comorbid depression and ALC have been associated with greater severity for both disorders [37].…”
Section: Discussionmentioning
confidence: 99%